Quantitative Dynamic Calculation Method of Ecological Compensation in Core River Basin Based on Pollutant Reduction Cost - HU Xin (Renmin Zhujiang)
In a core basin,the city agglomeration and developed economy often lead to huge resource consumption,which seriously damages the surrounding ecological resources.As the traditional quantitative dynamic calculation method of ecological compensation is greatly affected by the natural environment in the core basin,the accuracy of the quantitative calculation is poor.Therefore,a quantitative dynamic calculation method of ecological compensation for a core basin based on the reduction cost of pollutants is proposed.In this paper,the gray parameters of any pixel in a core basin image are described,and the feature extraction matrix is smoothed by the filtering function.By judging the quality of ecological compensation characteristics,the ecological compensation features in the core basin are extracted.Moreover,the gray threshold for the classification of ecological compensation features and the use conditions of parameters are given,and the plane component of the optimal ecological compensation feature is calculated.Then,the calculation method of pollutant reduction costs is applied to evaluate the loss caused by environmental pollution and vegetation damage in the core basin,and with the calculation of water conservation in the ecosystem,the ecological compensation of the core basin is calculated quantitatively and dynamically.The experimental results reveal that the method improves the accuracy of quantitative dynamic calculation of ecological compensation and shortens the calculation time.This indicates that the calculation performance of this method is superior,and it can provide accurate ecological supplementary suggestions and a basis for the ecological compensation analysis in the core area.